2019
DOI: 10.18178/ijmlc.2019.9.3.813
|View full text |Cite
|
Sign up to set email alerts
|

Handwritten Electric Circuit Diagram Recognition: An Approach Based on Finite State Machine

Abstract: In this paper we propose a method for recognizing hand drawn electronic circuit diagrams. The proposed method first detect and classify each components present in the hand drawn circuit diagram. For the purpose of component recognition, we have constructed the feature vector by combining Local Binary Pattern (LBP) and statistical features based on pixel density. Classification of components is done by using support vector machine (SVM) classifier. Upon detection and recognition of components, the proposed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…For example, only two studies [37], [38] report a higher accuracy rate than the accuracy rate for recognizing the BPMN element 'Exclusive gateway', which achieved a recognition accuracy of 95%. The recognition rates of BPMN elements 'Non-interrupting start time event' and 'User task' are slightly lower but comparable with results presented in [26], [34], [35], [36], while the accuracy rate for recognition of element 'Complex gateway' is comparable to the results presented in research [30] and [31]. Unfortunately, the results of the remaining investigated BPMN elements indicated a lower accuracy rate (< 76%) when compared to similar studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For example, only two studies [37], [38] report a higher accuracy rate than the accuracy rate for recognizing the BPMN element 'Exclusive gateway', which achieved a recognition accuracy of 95%. The recognition rates of BPMN elements 'Non-interrupting start time event' and 'User task' are slightly lower but comparable with results presented in [26], [34], [35], [36], while the accuracy rate for recognition of element 'Complex gateway' is comparable to the results presented in research [30] and [31]. Unfortunately, the results of the remaining investigated BPMN elements indicated a lower accuracy rate (< 76%) when compared to similar studies.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, some general parallels between the results of our work and related research can be made. In general, the average accuracy rate (61%) of all investigated BPMN elements is lower compared to similar research [26], [27], [28], [30], [31], [34], [36], [37], [38]. In the related research, the lowest accuracy rate was identified in research [27], where the system correctly identified 79% of the UML symbols.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The research efforts in this domain are not limited to digital circuits but they have been extended to recognize electrical circuits [15][16][17]. The authors in previous studies [15,16] applied image segmentation and feature extraction of electrical circuit elements (e.g., resistor and capacitor). The extracted features included the histogram of oriented gradients, local binary pattern (LBP), statistical features based on pixel density like scalar pixel-distribution, and vector relationships between straight lines in polygonal representations.…”
Section: Online Recognitionmentioning
confidence: 99%
“…The SVM, DT, and KNN machine learning algorithms used in the previously proposed techniques require careful and accurate feature selection and extraction in order to achieve acceptable recognition results. However, manually extracting the features as done previously [13][14][15][16][17] requires deep analysis of target elements. In addition, for each new digital block or circuit element the feature extraction procedure might be repeated with new features required to resolve conflicts and similarities.…”
Section: Online Recognitionmentioning
confidence: 99%